PERLINDUNGAN HUKUM TERHADAP KONSUMEN YANG MENGGUNAKAN SISTEM PEMBAYARAN PAYLATER MELALUI APLIKASI JUAL BELI ONLINE SHOPEE - Dharmadji, Tazkira Pradika; Sulistiyantoro, Hariyo (Gapenas Publisher, 2023)
There is a discrepancy between Shopee's policy regarding refunds for transactions made using Shopee Paylater and what buyers expect. Shopee's policy states that refunds for Shopee Paylater transactions will be in the form of balances or limits on Shopee Paylater. However, buyers hope to receive a refund Back at Paylater's shopee limit. When a buyer wants to return an item and get a refund for a Shopee Paylater transaction, they must first open a mediation case in the Resolution Center. After the case is resolved, the buyer still has to pay the Shopee Paylater bill. However, the billed amount will be converted to credit in the buyer's Shopee Paylater account. This differs from what buyers expect, as they are unable to receive a refund to their original payment method. The type of research used in writing this thesis is normative legal research. due to find out the legal position of using Paylater legally and produce a conclusion that is relevant to existing legal theories. This research is a legal research with a conceptual approach. The result of this research is that shopee should consider allowing buyers to receive refunds back to their original payment method, rather than converting refunds into credits in their Shopee Pay Later accounts. Pay later services are useful services for both consumers and sellers. The government has enacted regulations to protect this type of transaction. Consumers must be smart in choosing e-commerce and fintech service providers for pay later services to avoid problems